SIFAT KIMIA TANAH DAN PERKEMBANGAN AKAR KELAPA SAWIT (Elaeis guineensis Jacq.) PADA BERBAGAI DIMENSI RORAK DENGAN PEMBERIAN TANDAN KOSONG - Kurniawan, Eko; ', Ardian; ', Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The development of the root system of plants are a reflection of the level of physical and chemical soil properties. Siltpit (rorak) is a conservation pit of a certain size and layout which systematically provide benefits for soil remediation. Empty Fruit Bunch (Tan-kos) used as an alternative of organic fertilizer and also contribute to the improvement of physical - chemical and biological properties of soil. The experiments were conducted with four treatments and 4 replications . Experiment arranged in Radomized Completely Block Design with treatment EFB applications 750 kg on the soil surface with dimension 3mx2m (T0); siltpit size 3 m x 0.66 m x 0.75 m + 750 kg EFB (T1); siltpit size 5 m x 0.6 m x 0.5 m + 750 kg EFB (T2) and siltpit size 5 m x 1 m x 0.3 m + 750 kg EFB (T3). T2 treatment gives the most influence on the increase in the CEC of 4.8 cmol / kg then T0 of 2.8 cmol / kg. Improvement  P-dissolved  is found in T3 4:06 ppm followed by T0 3.96 ppm, K-total increase 0.75 cmol/kg and K-available in 0.9 cmol/kg.T0 treatment effect significant difference in diameter, wet weight, dry weight and root length tertiary depth of I, II and III. While treatment pit + 750 kg EFB (T1,T2 and T3) did not significant impact and significantly influence on the treatment T2 in parameter tertiary root length of 27.93 mm in depth III. Key words : Siltpit, EFB, root development and soil properties.